Original papersDAPT in the control of human hair follicle stem cell proliferation and differentiation - Jiang, Jindou; Miao, Yong; Xiao, Shune; Zhang, Zhidan; Hu, Zhiqi (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction : Stem cells from hair follicle have great therapeutic applications in regenerative medicine as sources of cells for transplantation. The differentiation pathway selected by hair follicle stem cells (HFSC) is largely determined by local microenvironmental signals. In this study, human hair follicle stem cells were treated with Notch signaling blocker to explore a new approach to modulate human hair follicle stem cell proliferation and differentiation in vitro . Aim: To define the functional consequences of blocking the Notch signaling pathway on the proliferation and differentiation of human HSCs. Material and methods : The human hair follicle stem cells were treated with various concentrations of Notch signaling blocker DAPT (24-diamino-5-phenylthiazole). The viability of the cells was investigated with clonogenicity assays. The expression of stem cell markers, cell cycle and cell apoptosis were analysed by flow cytometry. Results: Notch blocking leads to promotion of human hair follicle stem cell proliferation and inhibition of differentiation in response to DAPT. The maximum effect of DAPT on the viability of human HFSC was observed at a concentration of 20 M. We found that DAPT treatment results in downregulation of Hes1 and p21 and upregulation of Wnt10b. Conclusions : γ-Secretase inhibitor DAPT has a modulatory effect on the human HFSC. The DAPT may modulate human hair follicle stem cell proliferation and differentiation through regulation of p21 and Wnt-10b.